Upravljanje mestnih gozdov v Sloveniji - Simončič, Tina (Gozdarski vestnik, 2024)
Urban forests, which are designated as special purpose forests (SPFs) by local ordinances, account for 0.4% of Slovenia's total forest area. This paper analyses the state and the main characteristics of urban forest planning and management in Slovenia. We have analysed databases on urban forests, forest management plans, decrees on SPFs and other legal regulations governing the management of urban forests. We analysed in detail the characteristics of urban forest management in Ljubljana, Maribor, Celje and Novo mesto, taking into account the following criteria: i) forest condition, ii) legal status, iii) strategic plan for urban forests, iv) private forest purchase, v) compensation to forest owners, vi) management adaptation, vii) recreational infrastructure, viii) public relations, ix) urban forest as a brand. Based on the analysis, we suggest the following improvements to urban forest management in Slovenia: i) adoption or updating of relevant legal regulations, ii) intensification of cooperation between the Slovenia Forest Service and local communities, iii) advancement of the urban forest planning concept, iv) activation of forest stand management, v) ensuring appropriate conditions for adapted management in private forests, vi) improvement of the staff structure for the work in the urban forests, vii) improvement of inter-institutional cooperation and communication with the public.
Keywords: gozdnogospodarsko načrtovanje; mestni gozdovi; prilagojeno gospodarjenje; primerjalna analiza